1999
DOI: 10.1093/emboj/18.21.6106
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat transcriptional activity is regulated by acetylation

Abstract: The human immunodeficiency virus (HIV) trans- activator protein, Tat, stimulates transcription from the viral long-terminal repeats (LTR) through an RNA hairpin element, trans-activation responsive region (TAR). We and others have shown that trans-activator protein (Tat)-associated histone acetyltransferases (TAHs), p300 and p300/CBP-associating factor (PCAF), assist functionally in the activation of chromosomally integrated HIV-1 LTR. Here, we show that p300 and PCAF also directly acetylate Tat. We defined tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
398
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(418 citation statements)
references
References 65 publications
(144 reference statements)
18
398
0
2
Order By: Relevance
“…RNA binding proteins represent a new class of substrates for acetyltransferases. The HIV-1 viral RNA binding trans-activator protein, Tat, was shown to be a substrate for the acetyltransferases p300 and PCAF (Kiernan et al, 1999). Acetylation within the RNA binding domain of Tat by p300 inhibits Tat binding to the trans-activation responsive region (TAR) RNA, which promotes the transcription of viral messages (Kiernan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA binding proteins represent a new class of substrates for acetyltransferases. The HIV-1 viral RNA binding trans-activator protein, Tat, was shown to be a substrate for the acetyltransferases p300 and PCAF (Kiernan et al, 1999). Acetylation within the RNA binding domain of Tat by p300 inhibits Tat binding to the trans-activation responsive region (TAR) RNA, which promotes the transcription of viral messages (Kiernan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 viral RNA binding trans-activator protein, Tat, was shown to be a substrate for the acetyltransferases p300 and PCAF (Kiernan et al, 1999). Acetylation within the RNA binding domain of Tat by p300 inhibits Tat binding to the trans-activation responsive region (TAR) RNA, which promotes the transcription of viral messages (Kiernan et al, 1999). In contrast, acetylation of Sam68 by CBP in vitro appears to occur within the amino terminal region flanking the RNA binding domain ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…TSA is reported to act by allowing the acetylation of Tat, allowing dissociation from the Tat responsive element TAR after phosphorylation of the C-terminal domain of the RNA polymerase recycling Tat to act on another TAR. 38 If the Tat level of the cell is very low, then TSA would have limited substrate on which to inhibit the effect of histone deacetylases to affect transcription. Consistent with this, some preliminary data showed that applying TSA to cells with active integrated construct seemed to enhance their expression level (unpublished data).…”
Section: Gene Expression Of Integrated Hiv-1 Vector Hp Mok Et Almentioning
confidence: 99%
“…Le travail de Dennis Lo et al [4] ( Figure 1) utilise le génotypage par SNP (single nucleotide polymorphism) et la quantification des transcrits du gène PLAC4 (placenta specific protein 4) situé sur le chromosome 21, exprimés de façon prévalente au niveau du placenta et dont une proportion passe dans la circulation [5]. La méthode implique l'extraction des ARN du plasma, l'amplification par RT-PCR d'un locus SNP (rs8130833) sur le chromosome 21 (locus qui n'est informatif que dans 45 % de la population) et l'analyse quantitative par spectrométrie de masse des produits d'amplification.…”
Section: Quantification Des Transcrits Foetauxunclassified